The fan controller system using microcontroller (PIC16F877) / Norlaina Abdullah - Abdullah, Norlaina (2003)
Nowadays, personal computer (PC) become important to people in solving their job especially university students. Students used the PC to settle their assignments and surfing the net to find references in finishing their assignments, also to reply mail or playing games. If the PC tbr a long period, the processor in the Centre Processing Unit (CPU) will get hot, therefore a fan is used to cool the processor and avoid it from damage. However the fan produced a noise. This project presents the development of fan controller to control the fan speed via the temperature sensor. The circuit can control either automatically or manually and it is easy to used. The main components to perform this project are microcontroller (P1C16F877), temperature sensor, Pulse Width Modulation (PWM) and windows application, Visual Basic. The software is written in PIC language using MPLAB, which control the overall circuit. The software needs to be written and download into the microcontroller to operate the circuit. The window application is used Visual Basic C++ 6.0. From the results obtained in completing this project, it showed that the project has the potential in market, especially in Malaysia.